Analisis Stress, Displacement, dan Strain pada Piston dengan Variasi bahan Piston menggunakan Material Aluminium AA356.0-F, 2618-T61 (SS), 4032-T6 - Jaya Saputra, Trisma; Kurniyawan, Dwi; Akbar Mantofani, Rizal; Eko Prasetyo, Wahyu (Jurnal Etnik: Ekonomi-Teknik, 2023)
The purpose of this study is to analyze the mechanical response of a piston in an engine with different piston materials. The piston materials used are Aluminium AA356.0-F, 2618-T61 (SS), and 4032-T6. The analysis is conducted using the Solidworks software, which allows for simulation and evaluation of the piston's performance under operational conditions. Stress, displacement, and strain analysis of a piston using different piston materials (Aluminium AA356.0-F, 2618-T61 (SS), 4032-T6) conducted using Solidworks. Objective: gaining insights into the relative performance of each piston material and selecting the optimal material for engine applications. A 3D model of a piston is created using Solidworks, followed by the selection of three different materials: Aluminium AA356.0-F, 2618-T61 (SS), and 4032-T6. Simulation analysis is performed to obtain the stress, displacement, and strain for each variation of the piston material. The results are then analyzed and compared to determine the relative performance of each piston material. Analysis using Solidworks revealed significant variations in stress, displacement, and strain in pistons with Aluminium AA356.0-F, 2618-T61 (SS), and 4032-T6 materials. The 2618-T61 (SS) material exhibited higher stress, while the 4032-T6 material showed lower displacement. The selection of piston materials should consider factors such as strength, deformability, and optimal performance. The analysis using Solidworks showed significant differences in stress, displacement, and strain in pistons with varying piston materials. The selection of piston materials should consider a balance between strength and deformability for optimal performance.